Arbeitsgemeinschaft über das Klassenkörperturmproblem: 18. bis 23. Oktober 1964 - Roquette, Peter (Tagungsbericht, 1964)
R. Berger, Berlin; S. Böge, Heidelberg; W. Böge, Heidelberg; W. Felscher, Freiburg; G. Gaschütz, Kiel; G. Harder, Hamburg; K. Hoechsmann, Tübingen; W. Jehne, Heidelber; O. Kegel, Frankfurt a. M.; H. König, Köln; E. Kunz, Heidelberg; H. Kupisch, Saarbrücken; E. Lamprecht, Saarbrücken; H. Leptin, Hamburg; D. Puppe, Saarbrücken; P. Roquette, Tübingen